Dad and Kior (t. Yom. 2:2, m. Yom. 3:10): A Tannaitic Figurative Image - Haendler, Cecilia (Journal of ancient Judaism, 2023)
This article analyzes the expression dad la-kior (female breasts for the [Temple’s] laver) for its spigots (t. Yom. 2:2, m. Yom. 3:10), which so far has received no scholarly attention. The Temple’s laver has no taps/spigots in any attestation from the Bible to Josephus. The laver is an essential item in rabbinic imagery of the Temple and choreography of human-Divine communication. The term dad is used figuratively also for the Divine as nursing infant Israel through the manna (t. Sot. 4:3, Sif. Num. 89). The complete dependency of Israel on the Divine in the desert and of the infant on the breast parallels the laver as the crucial point on which Israel’s atonement depends. Ben Qatin (cf. Latin catīnus [basin]), who offers the laver, and other diasporic donors’ dependency on a literary Temple and rabbinic identarian normativity about handwashing are strengthened through a female image. This marks breastfeeding as a topos for exegetical competition.